The gamma subunit of DNA polymerase III holoenzyme of Escherichia coli is produced by ribosomal frameshifting. - Flower, A M (1990)
The tau and gamma subunits of DNA polymerase III holoenzyme are both products of the dnaX gene. Since tau and gamma are required as stoichiometric components of the replicative complex, a mechanism must exist for the cell to coordinate their synthesis and ensure that both subunits are present in an adequate quantity and ratio for assembly. We have proposed that gamma is produced by a translational frameshift event. In this report, we describe the use of dnaX-lacZ fusions in all three reading frames to demonstrate that gamma, the shorter product of dnaX, is generated by ribosomal frameshifting to the -1 reading frame of the mRNA within an oligo(A) sequence that is followed by a sequence predicted to form a stable secondary structure. Immediately after frameshifting a stop codon is encountered, leading to translational termination. Mutagenesis of the oligo(A) sequence abolishes frameshifting, and partial disruption of the predicted distal secondary structure severely impairs the efficiency. Comparison of the expression of lacZ fused to dnaX distal to the site of frameshifting in the -1 and 0 reading frames indicates that the efficiency of frameshifting is approximately 40%.